Analisis Literasi dan Inklusi Terhadap Keputusan Gen Z Berinvestasi Pada Reksadana Syariah - Selviana, Shela; Pertiwi, Ruspita Rani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The phenomenon of gen Z dominating the capital market indicates their high interest in investment activities even though there are still challenges in financial literacy and inclusion. This study aims to analyze the influence of Islamic financial literacy and inclusion on generation Z's investment decisions in Islamic mutual funds. The research was conducted in Yogyakarta, involving 100 respondents who are members of generation Z. The method applied in this study is regression analysis to examine the relationship between the variables of financial literacy, financial inclusion, and investment decisions. The research findings show that financial literacy has a significant positive effect on investment decisions, so that the higher the level of financial literacy, the greater the tendency of generation Z to invest in Islamic mutual funds. In addition, financial inclusion also contributes to improving investment decisions. This study identified that 61.7% of Generation Z's investment decisions are influenced by financial literacy and financial inclusion. These findings indicate the importance of education and accessibility of information on Islamic finance to encourage the younger generation to further improve Islamic financial literacy and inclusion in Indonesia.